2021
DOI: 10.1155/2021/5515467
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Watchful Waiting Approach vs. Antibiotic Therapy in Children with Nonsevere Acute Otitis Media: A Randomized Clinical Trial

Abstract: Objective. To compare both approaches for the treatment of nonsevere acute otitis media (AOM) in Iran. Methods. This randomized clinical trial was performed at a pediatric infectious diseases clinic in Buali tertiary hospital in Sari, north of Iran, from 2016 to 2018. All participants in this study were previously healthy children with AOM diagnosis, who were 6 months to 6 years old. The patients were randomly assigned into two groups: the intervention (80 mg/kg/day amoxicillin for 7-10 days) and the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Six studies included results for AM as a serious complication of AOM (2 RCTs and 4 observational studies), observing a total of 269 episodes of AM following 1,623,458 treated AOM episodes and 187 episodes of AM following 531,258 untreated AOM episodes [22, 24,25,42,47,53]. An additional 5 studies reported no AM, out of 630 controls and 610 treated AOM cases [37,39,46,51,52]. Antibiotics showed a protective effect for acute AM (RR 0.48, 95% CI 0.40-0.59), with an NNT of 5,368 (Fig 2A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies included results for AM as a serious complication of AOM (2 RCTs and 4 observational studies), observing a total of 269 episodes of AM following 1,623,458 treated AOM episodes and 187 episodes of AM following 531,258 untreated AOM episodes [22, 24,25,42,47,53]. An additional 5 studies reported no AM, out of 630 controls and 610 treated AOM cases [37,39,46,51,52]. Antibiotics showed a protective effect for acute AM (RR 0.48, 95% CI 0.40-0.59), with an NNT of 5,368 (Fig 2A).…”
Section: Discussionmentioning
confidence: 99%
“…For observational studies, the control groups included no antibiotic prescription/treatment and delayed treatment. Out of the 5 studies with delayed antibiotic therapy as the control group, 1 used a watchful waiting period of 72 hours [43] and 4 used 48 hours [15,41,45,46]. Co-interventions were allowed or encouraged in 18 studies, consisting of symptomatic treatment with analgesics, antipyretics, antihistamines, and decongestants.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies suggest that for certain children with non-severe AOM, a watchful waiting approach might be a viable alternative to immediate antibiotic therapy (5,6). Only one Iranian study on this issue revealed that faster recovery from AOM is achieved when antibiotics are prescribed, although the potential risk of side effects should be considered (7).…”
Section: Introductionmentioning
confidence: 99%